2007
DOI: 10.1111/j.1600-051x.2007.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of local and systemic factors on the incidence of oral implant failures, up to abutment connection

Abstract: The indication for the use of oral implants should sometimes be reconsidered when alternative prosthetic treatments are available in the presence of possibly interfering systemic or local factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
358
7
35

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(418 citation statements)
references
References 37 publications
18
358
7
35
Order By: Relevance
“…This is possibly due to bacterial contamination of the implant surface during the initial stages of healing 8,46) . A high rate of implant failure has been reported in sockets with periapical lesions, especially with placement of machined-surface implants 5) . Moreover, many studies have reported an increase in loss of endosseous implants at sites associated with periodontal disease 12,24,35) , whereas few have reported satisfactory results 13,20) .…”
Section: Introductionmentioning
confidence: 99%
“…This is possibly due to bacterial contamination of the implant surface during the initial stages of healing 8,46) . A high rate of implant failure has been reported in sockets with periapical lesions, especially with placement of machined-surface implants 5) . Moreover, many studies have reported an increase in loss of endosseous implants at sites associated with periodontal disease 12,24,35) , whereas few have reported satisfactory results 13,20) .…”
Section: Introductionmentioning
confidence: 99%
“…When it happens before or at abutment insertions, it is considered as an early failure, and it may be attributed to drawbacks which occur during osseointegration healing phase. On the other hand, after occlusal loading [Table/ Fig-2], any problem which occurs with the implant-prosthesis set is considered as a late failure, and it is related to any process that may affect the maintenance of previously established osseointegration [11].…”
Section: Discussion Aetiologymentioning
confidence: 99%
“…Alssadi et al, [11] To assess the influence of systemic and local bone and intra-oralfactors on the occurrence of early implant failures, i.e. up to the abutmentconnection.…”
Section: Discussion Aetiologymentioning
confidence: 99%
“…18 Late implant loss has been associated with occlusal overload, peri-implantitis, poor bone quantity and poor bone quality. 18,22 The reported survival rates for implants supporting crowns and fixed partial dentures exceed 95% over 5 years 2,6,7 and 93% over 10 years. 6,7 However, survival does not equate to success and these rates must be interpreted cautiously because a surviving implant may be failing, unrestorable or may have had extensive remedial treatment.…”
Section: Implant Lossmentioning
confidence: 99%
“…16 When implant loss occurs, it occurs before functional loading in approximately 55% of cases. 4,22 When an implant fails an alternative treatment may be considered, the site may be allowed to heal before placing a new implant (Figs 10 and 11) or a new, wider implant may be placed immediately. 23 There is limited evidence to suggest that implants placed at the site of previously failed implants have lower survival rates.…”
Section: Implant Lossmentioning
confidence: 99%